Evaluation of the reproductive cycle and gonadal development in the climbing perch, Anabas testudineus (Bloch, 1792) in captivity - Chokki Veettil Priyatha; Kumari Chidambaran Chitra (Journal of Fisheries, 2022)
The climbing perch Anabas testudineus, the most demanded indigenous fish species of India, were used for the evaluation of reproductive strategy and gonadal development at first maturation under the controlled laboratory condition. In both sexes, four distinct gonadal developmental stages namely preparatory, pre-spawning, spawning, and post-spawning were identified based on the gonadosomatic index (GSI), hepatosomatic index (HSI), gonadal morphology, and the levels of serum sex hormones. The spawning stage was identified from July and August and the fecundity ranged from 6500–11000 eggs. The GSI exhibited a significant increase from preparatory to pre-spawning and spawning stages, and maintained high until August. The HSI was maintained the same during preparatory, pre-spawning, and spawning stages while increased in post-spawning stage in both sexes. Serum estrogen and testosterone levels increased significantly during pre-spawning, and spawning stages in both sexes. Fecundity showed a positive correlation with the length, weight, and ovary weight. Histological sections showed that male A. testudineus were group-synchronous spawners. Both sexes showed discrete reproductive cycles characterized by distinct changes in gonadal size, sex hormones and gonadal indices. This study will bridge the gap of insufficient knowledge to support the best practices suitable for the A. testudineus culture and survival under captivity.